Nanomedicine: promises and pitfalls 3 - Webster, Thomas J. (Henry Stewart Talks, 2015)
Bacteria-inhibiting nano materials, Nanostructured silicon nitride, Electrophoretic deposition, Nanoscale radio-opaque agents, Pure polymers and bacteria, Nanostructured selenium coating, Antibacterial efficacy of free magnesium oxide (MgO), Titanium & vascular endothelial cell proliferation, Nano-structured PGA & tissue regeneration, Fighting Ebola with nanotechnology